Retention in HIV care among Southeast Asian people living with HIV: A systematic review and meta-analysis - Sidik Maulana; Kusman Ibrahim; Iqbal Pramukti; Shakira Amirah; Yovita Hartantri (Belitung Nursing Journal)
Background: Despite the effectiveness of antiretroviral therapy (ART) in reducing HIV-related morbidity and mortality, the retention of HIV care remains suboptimal in Southeast Asia.